2018
DOI: 10.20944/preprints201805.0091.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Markov Chain and Techno-Economic Analysis to Identify the Commercial Potential of New Technology: A Case Study of Motorcycle in Surakarta, Indonesia

Abstract: LiFePO4 (LFP) or Lithium-ion battery with its advantages compared to common current motorcycle battery is an appropriate alternative in substituting wet and dry cell battery. Huge amount of demand of motorcycle along with the battery in Indonesia also make it an interesting product for business. In order to assess the commercial potential for such a new technology, market share needs to be estimated as well as the techno-economic feasibility. Hence, market share prediction using the residents of Surakarta Regi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This research found the informants using purposive sampling techniques with snowball sampling models, namely the use of informants that multiply after research is carried out in the field [9]. The problem analysis used understanding, contextual and matching methods.…”
Section: Methodsmentioning
confidence: 99%
“…This research found the informants using purposive sampling techniques with snowball sampling models, namely the use of informants that multiply after research is carried out in the field [9]. The problem analysis used understanding, contextual and matching methods.…”
Section: Methodsmentioning
confidence: 99%